2008
DOI: 10.1111/j.1466-7657.2008.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in children's fatigue during the course of treatment for paediatric cancer

Abstract: Cancer treatment was found significantly to increase children's fatigue levels. Medical procedures and the hospital environment seemed to be major causative factors of the fatigue experienced by children with cancer during their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
2
24
0
3
Order By: Relevance
“…anemia) 34 and symptoms. 7,32,35 Our findings, in conjunction with those of others, underscore the complex and multifactorial nature of fatigue.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…anemia) 34 and symptoms. 7,32,35 Our findings, in conjunction with those of others, underscore the complex and multifactorial nature of fatigue.…”
Section: Discussionsupporting
confidence: 80%
“…The mechanism by which a child with a high burden of other symptoms is more likely to experience fatigue distress is not well understood but has been previously described. 35 Suffering from a different symptom may reduce a child’s threshold for experiencing fatigue distress (and vice versa). Treatment of other symptoms (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue problems during hospitalization may be attributed to higher chemotherapy intensity and treatment related symptoms, compared with outpatient treatments (Collins, et al, 2000). Medical procedures during hospitalization such as lumbar punctures, bone marrow aspirations, and repetitive blood draws were causing pain and stress, leading to fatigue (Perdikaris et al, 2008). Adolescents reported that the hospital environment and the lack of interesting activities were the main causes of fatigue (Hockenberry-Eaton et al, 2000; Perdikaris et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The childhood fatigue scale was used to assess fatigue in 40 children (7e12 y) being treated for cancer, including chemotherapy and/or radiotherapy [78]. Children diagnosed with brain tumours were excluded.…”
Section: Fatigue In Children With Cancermentioning
confidence: 99%